(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2020)
3D printing can be used to manufacture both standard devices, as well as personalized devices. For the latter, a number of jurisdictions around the world allow those products to enter the market not following a normal conformity assessment. As an example, the EU has the system of custom-made devices. As regulators realize that 3D printing leads to a strong growth in personalized devices, these regimes have become more restrictive. This presentation aims to provide a brief overview for some jurisdictions, including the EU, USA and Australia.